PERBEDAAN SPESIFIC VALUES ANTARA MAHASISWA AKUNTANSI DAN MAHASISWA KEDOKTERAN: STUDI EMPIRIS PADA UNIVERSITAS GADJAH MADA - Siti Fathonah (Faculty of Economics and Business, Universitas Gadjah Mada, 2004)
This study aims to analyze, to compare and to differentiate specific values of accounting and medical students. While the majority of previous studies used the Rokeach Instrument Survey, the current study employs the modified Rokeach and Schwartz Instrument. This modified instrument consists of thirty variables. However, a factor analysis indicates that the variables can be grouped into four constructs: individuality, theoretical, social, and esthetical. Overall, the study shows that personal values of accounting students are below those of medical students. Based on the finding, the study suggests that a certain subject or course with a high ethical contents should be taught in accounting programs.